Quartz Dust Exposure Affects NLRP3 Inflammasome Activation and Plasma Levels of IL-18 and IL-1Ra in Iron Foundry Workers. (7th January 2020) - Hedbrant, Alexander; Andersson, Lena; Bryngelsson, Ing-Liss; Eklund, Daniel; Westberg, Håkan; Särndahl, Eva; Persson, Alexander
Abstract : Purpose . To study the association between inhalation of particulate matter or quartz in Swedish iron foundries and the effects on NLRP3 inflammasome activation. Methods . Particle exposure measurements were performed during an eight-hour work day for 85 foundry workers at three Swedish iron foundries. Personal sampling was used for measurement of respirable quartz and dust and stationary measurements to obtain exposure measurements for inhalable dust and PM10 . The NLRP3 inflammasome markers, interleukin- (IL-) 1 β and IL-18, and inhibitors IL-1 receptor antagonist (IL-1Ra) and IL-18 binding protein (IL-18BP) were measured in plasma. Inflammasome activation was measured by caspase-1 enzymatic activity in monocytes in whole blood by flow cytometry, and expression of inflammasome-related genes was quantified using real-time PCR. Multiple linear regression analysis was used to investigate associations between PM exposures and inflammatory markers. Sex, age, smoking, current infection, BMI, and single nucleotide polymorphism in the inflammasome regulating genes CARD8 (C10X) and NLRP3 (Q705K) were included as covariates. Results . The average exposure levels of respirable dust and quartz were 0.85 and 0.052 mg/m 3, respectively. A significant exposure-response was found for respirable dust and IL-18 and for inhalable dust and IL-1Ra. Whole blood, drawn from study participants, was stimulated ex vivo with inflammasome priming stimuli LPS or Pam3CSK4, resulting in a 47% and 49% increase in caspase-1 enzymatic activity in monocytes. This increase in caspase-1 activity was significantly attenuated in the higher exposure groups for most PM exposure measures. Conclusions . The results indicate that exposure levels of PM in the iron foundry environment can affect the NLRP3 inflammasome and systemic inflammation.